2020
DOI: 10.37546/jaltjj42.2-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cooperative Learning on Self-Efficacy in an EFL Classroom

Abstract: The objective of this study was to determine whether incorporating cooperative learning approaches positively influences the perceived self-efficacy of learners taking part in a compulsory English language program at the university level. This study tested the hypothesis that implementation of strategies fostering language skill development through cooperative learning leads to an increase in student self-efficacy. Qualitative and quantitative methods were employed to investigate this hypothesis in treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, she exposed students to real-life problems that could positively impact their motivation and achievement. Other studies also demonstrated that cooperative learning positively influences learning vocabulary (Gashti, 2021), oral skill (Moghaddam & Heidari, 2018), critical thinking (Nazari et al, 2021), and self-efficacy in the EFL classroom (Saunders-Wyndham & Smith, 2020). Possible explanations for discrepancies in research findings include the fact that people from different cultures cooperate in different ways (Phuong-Mai et al, 2009) and that major complicated relationships exist between culture and the social components of cooperative group activity (Ghahraman & Tamimy, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, she exposed students to real-life problems that could positively impact their motivation and achievement. Other studies also demonstrated that cooperative learning positively influences learning vocabulary (Gashti, 2021), oral skill (Moghaddam & Heidari, 2018), critical thinking (Nazari et al, 2021), and self-efficacy in the EFL classroom (Saunders-Wyndham & Smith, 2020). Possible explanations for discrepancies in research findings include the fact that people from different cultures cooperate in different ways (Phuong-Mai et al, 2009) and that major complicated relationships exist between culture and the social components of cooperative group activity (Ghahraman & Tamimy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, when a group is composed of students who lack social skills, the efficacy of the group’s work is questioned (Johnson & Johnson, 2006; Lynn Brown, 2021). Thus, for the group to work well, students should have a sufficient level of communication, group, and social skills, which can be innate, taught and learned (Neo et al, 2012; Saunders-Wyndham & Smith, 2020). According to Killen (2007), these abilities must be taught.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation